Boronate derivatives of functionally diverse catechols: Stability studies - Ketuly, Kamal A.; Hadi, A.H.A. (2010)
Benzeneboronate of catecholic carboxyl methyl esters, N-acetyldopamine, coumarin and catechol estrogens were prepared as crystalline derivatives in high yield. Related catechol compounds with extra polar functional group(s) (OH, NH2) do not form or only partially form unstable cyclic boronate derivatives.